Further VAR evidence for the effectiveness of a credit channel in Germany - Oliver Holtemöller (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2002)
In this paper, the empirical relevance of the credit channel for the explanation of monetary policy transmission in Germany during the period of monetary targeting from 1975 to 1998 is analyzed. While existing studies of the credit channel rely mostly on the analysis of monetary policy effects on balance sheet items, both quantities and financing costs are considered here. Using vector autoregressive models, impulse response analysis and forecast error variance decompositions, strong empirical evidence for the effectiveness and relevance of a credit channel in Germany can be reported.
urn:nbn:de:kobv:11-10049290
Keywords: C32; E44; E52; 330; vectorautoregressive models; Credit channel; monetary policy transmission; money channel